Tratamiento informativo de medios impresos de Riobamba frente a la aprobación del matrimonio civil igualitario período mayo-octubre 2019 - Josselyn Gabriela, Romero Villa (2021)
ABSTRACT This research entitled informative treatment of print media of Riobamba versus the approval of equal civil marriage period May-October 2019 arose from the need to know how the press handle information on the approval of this right, where there was a lot of reaction from society both for and against this issue. We worked with a qualitative methodology because we collected data attributes of the topic investigated to identify how the information treatment was, in turn identifying which components were used at the time of publication of the information. The techniques used were documentary research, content analysis, and interviews with expert professionals related to the topic ordered in matrices of similarities and differences. This work was recognized that the print media in Riobamba had improved their informative treatment. However, terms that exclude the LGBTI community are still used, in addition to the printed ones gave more space to the church than to the homoparental couples. As a proposal, in the end, a short film was made. Where showed the advance of the printed media in the treatment of this information. Keywords: LGBTI, print media, information treatment, law, equal marriage. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980